Transition-metal-catalyzed synthesis of quinazolines: A review - Tamatam, Rekha; Kim, Seok-Ho; Shin, Dongyun (Frontiers in Chemistry, 2023)
Quinazolines are a class of nitrogen-containing heterocyclic compounds with broad-spectrum of pharmacological activities. Transition-metal-catalyzed reactions have emerged as reliable and indispensable tools for the synthesis of pharmaceuticals. These reactions provide new entries into pharmaceutical ingredients of continuously increasing complexity, and catalysis with these metals has streamlined the synthesis of several marketed drugs. The last few decades have witnessed a tremendous outburst of transition-metal-catalyzed reactions for the construction of quinazoline scaffolds. In this review, the progress achieved in the synthesis of quinazolines under transition metal-catalyzed conditions are summarized and reports from 2010 to date are covered. This is presented along with the mechanistic insights of each representative methodology. The advantages, limitations, and future perspectives of synthesis of quinazolines through such reactions are also discussed.